Pengaruh struktur modal, likuiditas, ukuran perusahaan, dan profitabilitas terhadap nilai perusahaan - Mahanani, Heni Tri; Kartika, Andi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The value of the company is a very importand part for the company, because it can be a reference for investors to see the survival of a company in the coming year. For example in manufacturing companies in the banking sector. To see the increasing value of the company, external and internal parties will pay attention to several factors that can affect the value company. This study aims to examine and analyze the effect of capital structur, liquidity, firm size, and profitability on firm value. The population used in this study are manufacturing companies in the banking sector listed on the Indonesian Stock Exchange for the period 2018-2021. The sample used is 138 using the purposive sample method. The data analysis technique used multiple regression analysis yechnique using the SPSS 16 program.the resut obtained in this study are the capital structure has no effect on firm value, liquidity has a significant positive effect on value, firm size has a significant positive effect on firm value, and profitability does not affect the value of the company.